Relationship between Serum Ferritin and Thyroid Hormones: A Hospital Based Cross Sectional Study - Dhakal, Sarita; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2024)
Abstract Background: Thyroid gland is one of the major endocrine gland, which plays a key role in growth, differentiation, development, and maintenance of body homeostasis. Trace elements like iron, selenium, iodine and zinc are needed for the normal functioning of the thyroid glands. So, deficiencies of these elements can impair thyroid functions. Objectives: The objective of our study was to assess the relationship between serum ferritin and thyroid hormones. Materials and methods: A descriptive cross-sectional study was carried out in the department of Biochemistry of College of Medical Sciences in Bharatpur, Chitwan, Nepal, from 1st June, 2023 to 1st December 2023. The patient visiting to medicine OPD were included and patients with confirmed case of thyroid disorder and iron deficiency anemia were excluded from the study. Conclusion: In our study there was statistically significant relationship between iron deficiency anemia and hypothyroidism. So, Ferritin level should be assessed in hypothyroid subjects. Keywords: Serum Ferritin, Thyroid hormones, Hypothyroidism,